2001
DOI: 10.1123/nirsa.25.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Student Benefits from University Recreation

Abstract: Research that determines the benefits that undergraduate students gain from participation in university recreation and its importance is needed to defend the existence of university recreation and to align oneself for further growth. Current data is one of the most important documented criteria needed to substantiate an increased operating budget, to justify adding personnel, and to validate the need for additional or new facilities. The goal of this research article is to respond to the need for current data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 5 publications
2
50
0
9
Order By: Relevance
“…A number of recent studies have focused on usage of CRFs as it relates to student learning, development, and academic success (Artinger, Clapham, Meigs, Sampson, & Forrester, 2006;Belch, Gebel, & Mass, 2001;Bryant et al, 1995;Haines, 2001;Hall, 2006;Lindsey & , 2006). Several of these studies specifically examined the relationship between CRF usage and quantifiable measures of student success, including persistence and GPA.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of recent studies have focused on usage of CRFs as it relates to student learning, development, and academic success (Artinger, Clapham, Meigs, Sampson, & Forrester, 2006;Belch, Gebel, & Mass, 2001;Bryant et al, 1995;Haines, 2001;Hall, 2006;Lindsey & , 2006). Several of these studies specifically examined the relationship between CRF usage and quantifiable measures of student success, including persistence and GPA.…”
Section: Literature Reviewmentioning
confidence: 96%
“…They concluded that CRF facilitate social integration by creating large numbers of opportunities for members of college communities to interact. In separate studies concerning the effect that CRFs have on students, Haines (2001) and Lindsey and Sessoms (2006) reported responses to the same survey question, "In deciding to continue at (your institution), how important to you was the availability of recreational facilities and programs?" Haines reported that 75 percent of males and 62 percent of females responded "somewhat important" or "very important" to the question.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Although the benefits of participating in recreational sports programs have been linked to a variety of leadership skills (Bryant, Banta, & Bradley, 1995;Cornelius, 1995;Downs, 2003;Haines, 2001), there is little empirical evidence documenting the benefits of students serving in leadership roles as officers of club sport programs (HallYannessa & Forrester, 2004Shertzer & Schuh, 2004) and no research on students serving in other volunteer leadership capacities within campus recrea tional sports programs. An omission from the student leadership literature has been an exami nation of the wide variety of leadership roles found in a college recreational sports program.…”
Section: A Constructivist Case Study Examining the Leadership Developmentioning
confidence: 97%
“…A number of recent studies have focused on usage of CRFs as it relates to student learning, development, and academic success (Artinger, Clapham, Meigs, Sampson, & Forrester, 2006;Belch, Gebel, & Mass, 2001;Bryant et al, 1995;Haines, 2001;Hall, 2006 , 2006). Several of these studies specifically examined the relationship between CRF usage and quantifiable measures of student success, including persistence and GPA.…”
Section: Literature Reviewmentioning
confidence: 99%